Photoelectrocatalytic degradation of pharmaceuticals and inactivation of viruses in water with tungsten oxide electrodes. Issue 3 (June 2022) - Tolosana-Moranchel, A.; Pichel, N.; Lubarsky, H.; Byrne, J.A.; Fernández-Ibañez, P.
Abstract: Electrochemically assisted photocatalysis (EAP) is one approach to overcome the fast recombination rates in photocatalysis and increase the quantum efficiency to produce ROS. In comparison to TiO2, tungsten trioxide (WO3 ) can utilize UV and visible photons and with EAP the external bias can be used to drive the reduction pathway. In this work WO3 electrodes were prepared hydrothermally on FTO. Vertically grown WO3 nanoplate-like structures were thoroughly characterized. The WO3 photoanodes improved photocurrent response compared to P25 and a visible response was measured. These results were attributed to smaller charge transfer resistance and their morphology. The activity of the photoanodes was assessed on the EAP degradation of sulfamethoxazole and MS2 bacteriophage. WO3 yielded ten times higher degradation rates for sulfamethoxazole (2.21 · 10 −6 mmol cm −2 min −1 ) compared to P25. WO3 also yielded the fastest MS2 inactivation rate. A rapid 5-log removal was achieved in 6 min with WO3 that maintained activity over 5 cycles. Graphical Abstract: ga1 Highlights: WO3 plate-like structures were successfully prepared by a hydrothermal method Plate-like WO3 morphology led to faster migration of charges towards the substrate Higher IPCE and APCE were obtained for WO3, able to absorb radiation up to 470 nm WO3 yielded faster reduction of MS2 and sulfamethoxazole than P25 electrodes WO3 photoanodes showed high stability and durability